Impact of sunspots on the incidence of autism in the human population - Zamfirov, Milen; Belenska-Todorova, Lyudmila (International Journal of Innovative Research and Scientific Studies, 2025)
Autism spectrum disorder (ASD) is a neurodevelopmental impairment with unclear etiology in which genetic and environmental factors are involved. The purpose of the current study is to investigate the relationship between solar activity and the incidence of autism. The Sun periodically increases its irradiance, following eleven-year cycles, during which significant shifts in solar activity result in magnetic storms on its surface known as sunspots. Changes in solar activity may affect people, causing physiological disturbances. For the study, individuals with neurodevelopmental disorders registered in centers for the assistance of persons with disabilities in Bulgaria were studied over a twenty-year period, from 2003 to 2024. The statistical analyses showed a correlation between the births of children with disabilities and solar activity, where the increase in the incidence of autism immediately follows periods of a high number of sunspots. We suggest further investigation of the impact of solar radiation on the predisposition to ASD development and its specific behaviors. Our findings provide predictability of the deterioration of autistic manifestations depending on solar activity.